If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -1x = -17 Solving -18 + -1x = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -1x = -17 + 18 Combine like terms: -18 + 18 = 0 0 + -1x = -17 + 18 -1x = -17 + 18 Combine like terms: -17 + 18 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| V-x-y+z=4 | | 4x=21+sqrt(56-x) | | 6x+2(5x-18)=56 | | 7z+2=23 | | 1000+100w=5000 | | D+00.2d=510 | | 15x^2+7=0 | | (2x+5)*(4x-3)=0 | | 24+4x=4x | | 10000+100w=5000 | | b=b^2 | | 2x-49=17 | | 2c^2=-3c | | 4(T-5)+2=-9+c+5 | | 2x+6=-38 | | x^2+x^2-14x-49=169 | | 6x+7(-2x-17)=-175 | | 13x^2+39x=0 | | 3(j-6)=j+10 | | (2x+8)(2x+7)= | | 3q^2-6q=0 | | 20+5x=55 | | cox(2x)-9=0 | | 2x+5=11x-4 | | 3x-4-(2x+3)=0 | | 100x=0.81 | | 7500.00+155.00=92440 | | C=240+8k | | f(x)=tan^2(x)-3 | | f(x)=tan^2(x-3) | | x^3+8x^2-14x-12=0 | | 5x+10=7x-70 |